The impact of governmental venture capital on innovative young firms growth - Yazdani, Leila (Medwell Journals, 2016)
Governments globally have established funds known as Governmental Venture Capital (GVC) and are significantly emphasizing on them in order to grow of young firms and also fulfill the gap of equity capital of new and innovative organizations. We find that firms backed by governmental venture capital reduce efficiency however increase innovation, job creation and job empowerment of young firms.